2003
DOI: 10.1038/oby.2003.140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Objective and Subjective Social Status on Obesity in a Biracial Cohort of Adolescents

Abstract: Objective: To characterize the associations between socioeconomic status (SES), two levels of subjective social status (SSS), and adolescent obesity. Research Methods and Procedures: Cross‐sectional study of 1491 black and white adolescents attending public school in a suburban school district in Greater Cincinnati, Ohio. BMI ≥95th percentile derived from measured height and weight defined overweight. Students rated SSS on separate 10‐point scales for society and school. A parent provided information on parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
217
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(235 citation statements)
references
References 30 publications
(44 reference statements)
15
217
1
2
Order By: Relevance
“…The basis for ethnic disparities in food consumption could be attributed to the fact that a larger number of African Americans were in the lower income group than European Americans (as observed in our study and also in previously published studies [58]) and hence may have consumed poorer diets (19) due to their inability to afford more healthful foods. Some other environmental factors like geographic reasons may also be responsible for these ethnic differences in food consumption.…”
Section: Discussionmentioning
confidence: 65%
“…The basis for ethnic disparities in food consumption could be attributed to the fact that a larger number of African Americans were in the lower income group than European Americans (as observed in our study and also in previously published studies [58]) and hence may have consumed poorer diets (19) due to their inability to afford more healthful foods. Some other environmental factors like geographic reasons may also be responsible for these ethnic differences in food consumption.…”
Section: Discussionmentioning
confidence: 65%
“…Nevertheless, an increasing body of research, mostly cross-sectional, indicates that SSS (measured as a ladder score) relates over and above objective SES markers to self-rated health (Franzini & FernandezEsquer, 2006;Hu et al, 2005;Operario, Adler, & Williams, 2004;Ostrove et al, 2000;SinghManoux, Marmot, & Adler, 2005), mental health (Franzini & Fernandez-Esquer, 2006;SinghManoux et al, 2005), heart rate and sleep latency (Adler, Epel, Castellazzo, & Ickovics, 2000), cortisol levels (Wright & Steptoe, 2005), and dental outcomes (Sanders, Slade, Turrell, Spencer, & Marcenes, 2006). Also, there is evidence that SSS relates to adolescent health (Goodman, Adler, Daniels, Morrison, Slap, & Dolan, 2003;Goodman, Adler, Kawachi, Frazier, Huang, & Colditz, 2001). In contrast, research has shown that SSS is not related at all to body mass index, sleep quality, and resting systolic blood pressure in women , angina and respiratory illness in women (Singh-Manoux et al, 2003), and difficulties in Activities of Daily Living (Hu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent study, the FAS appeared to be useful as a measure of SEP for Korean adolescents (Cho and Khang, 2010). However, there is growing evidence that youths' smoking was more significantly associated with subjective SEP than objective SEP itself (Goodman et al, 2003;Adler et al, 2000). Although the objective SEP is negatively related with smoking during adolescence , the objective SEP ignores the personal perception of one's place in the society (Goodman et al, 2003;Goodman et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…However, there is growing evidence that youths' smoking was more significantly associated with subjective SEP than objective SEP itself (Goodman et al, 2003;Adler et al, 2000). Although the objective SEP is negatively related with smoking during adolescence , the objective SEP ignores the personal perception of one's place in the society (Goodman et al, 2003;Goodman et al, 2007). In adolescence, one's social position among peers may be of a greater importance to health outcome than the parent's objective social position (Glendinning et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation